PENGARUH PENGGUNAAN APLIKASI AKUNTANSI DIGITAL TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN UMKM DI PURWODADI DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERATOR - Sari, Lusi Permata; Ifada, Luluk Muhimatul (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: Digital transformation in MSME financial management is one of the important adaptive strategies amidst the challenges of business efficiency and accountability. This study aims to analyze the effect of the use of digital accounting applications on the effectiveness of MSME financial management in Purwodadi, by considering financial literacy as a moderator variable. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with 10 MSME actors who use digital accounting applications, such as Kasir Pintar. Data analysis was carried out through data reduction, data presentation, and drawing thematic conclusions. The results of the study showed that the majority of informants felt significant benefits from the use of digital accounting applications in improving administrative efficiency, transaction recording accuracy, and ease of financial reporting. In addition, the level of financial literacy has been shown to strengthen the effectiveness of the use of this technology, where business actors with better financial understanding are able to optimize application features more optimally. The conclusion of this study confirms that the synergy between the use of digital accounting technology and adequate financial literacy can substantially improve the performance of MSME financial management. This study contributes to the development of digital-based accounting science as well as practical implications for strengthening MSME capacity through integrated financial education and technology interventions .Keywords: Digital accounting applications, effectiveness of financial management, financial literacy, MSMEs.